2011
DOI: 10.1016/j.visres.2011.06.002
|View full text |Cite
|
Sign up to set email alerts
|

Spatial frequency and visual discomfort

Abstract: Images created from noise filtered to have an approximately 1/f amplitude spectrum were altered by adding excess energy concentrated at various spatial frequencies. The effects of this manipulation on judgements of visual discomfort were studied. Visual noise with a 1/f amplitude spectrum (typical of natural images) was judged more comfortable than any image with a relative increase in contrast energy within a narrow spatial frequency band. A peak centred on 0.375-1.5cycles/degree of spatial frequency was cons… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

13
80
0

Year Published

2013
2013
2024
2024

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 83 publications
(98 citation statements)
references
References 52 publications
13
80
0
Order By: Relevance
“…This finding is consistent with research on the dose-response curve for the impact of tree cover density on stress reduction [13]. It is important to note that these perceptual and neural mechanisms are believed to be "automatic" and consistent across individuals and populations in the absence of disorders [1,3,5,14,17,26,27].…”
Section: Psychology Of Scene Perception and Preferencesupporting
confidence: 80%
See 1 more Smart Citation
“…This finding is consistent with research on the dose-response curve for the impact of tree cover density on stress reduction [13]. It is important to note that these perceptual and neural mechanisms are believed to be "automatic" and consistent across individuals and populations in the absence of disorders [1,3,5,14,17,26,27].…”
Section: Psychology Of Scene Perception and Preferencesupporting
confidence: 80%
“…with modern advancements in smartphone technology. We take into account a diverse set of literature looking at (1) visual reward circuits in the human brain that preferentially respond to some types of scenes [5], (2) how the human brain processes visual characteristics of scenes [27], and (3) the way that images of the environment may be analyzed and related to the activation of neural circuits responsible for positive and negative emotions [14,17,27].…”
Section: Psychology Of Scene Perception and Preferencementioning
confidence: 99%
“…By exchanging the phase and amplitude of comfortable and uncomfortable images, they showed that the discomfort was determined by the amplitude rather than the phase information. O'Hare and Hibbard 15 used images constructed from filtered noise and controlled for the apparent contrast of the stimuli. They also found that an excess of energy at mid-spatial frequencies determined discomfort ratings, although with a spatial frequency tuning that was slightly lower than that obtained by Fernandez and Wilkins.…”
Section: Visual Discomfort and 1/fmentioning
confidence: 99%
“…Individuals with trypophobia report that the visual quality and spatial properties of such stimuli trigger discomfort. [2][3][4][5] This may differ from phobic or aversive responses to a range of other stimuli, such as small animals, where the individual is uncomfortable in the presence of a non-visible animal. It has been suggested that trypophobia involves images with a particular spectral profile rather than clusters of holes per se.…”
Section: Introductionmentioning
confidence: 99%